Underground infrastructure of urban areas : selected and edited papers from the International Conference on Underground Infrastructure of Urban Areas, Wrocław, Poland, 22-24 October 2008 /: selected and edited papers from the International Conference on Underground Infrastructure of Urban Areas, Wrocław, Poland, 22-24 October 2008. (©2009) - Unknown
No abstract available